Learning Curves, Personal Characteristics, and Job Performance - Kostiuk, Peter F.; Follmann, Dean A. (Journal of Labor Economics, 1989)
Data on Naval Reserve recruiters are used to estimate the effects of on-the-job learning, experience, and individual characteristics on job performance. Generalizations of the Poisson distribution form the basis for estimating the effects of explanatory variables and control for individual heterogeneity and overdispersion. The findings show strong learning effects during the first 2 years on the job. Furthermore, lower pay-grade individuals have steeper learning curves than individuals in higher pay grades. Estimates of individual differences in productivity show a large variance in unobserved ability.